2019
DOI: 10.1002/hbm.24888
|View full text |Cite
|
Sign up to set email alerts
|

Neurostructural correlates of optimism: Gray matter density in the putamen predicts dispositional optimism in late adolescence

Abstract: Dispositional optimism reflects one's generalized positive expectancies for future outcomes and plays a crucial role in personal developmental outcomes and health (e.g., counteracting related mental disorders such as depression and anxiety). Increasing evidence has suggested that extraversion is an important personality factor contributing to dispositional optimism. However, less is known about the association between dispositional optimism and brain structure and the role of extraversion in this association. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 150 publications
(280 reference statements)
1
18
1
Order By: Relevance
“…Correspondingly, we suggest that a higher volume of the putamen may predispose individuals toward a larger personal optimism bias via an exacerbated weighing of reward and value. Notably, our findings for the left putamen are in line with a recent VBM study that reported how trait optimism positively correlated with gray matter density in bilateral putamen, with a stronger effect in the left putamen [49]. Furthermore, there is mounting evidence of putamen volumes being negatively associated with depression [67][68][69][70], a condition notorious for its pessimistic expectancies [71,72] and a lack of asymmetrical update of beliefs in the optimistic direction [73].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Correspondingly, we suggest that a higher volume of the putamen may predispose individuals toward a larger personal optimism bias via an exacerbated weighing of reward and value. Notably, our findings for the left putamen are in line with a recent VBM study that reported how trait optimism positively correlated with gray matter density in bilateral putamen, with a stronger effect in the left putamen [49]. Furthermore, there is mounting evidence of putamen volumes being negatively associated with depression [67][68][69][70], a condition notorious for its pessimistic expectancies [71,72] and a lack of asymmetrical update of beliefs in the optimistic direction [73].…”
Section: Discussionsupporting
confidence: 91%
“…Notably, the findings of the current study do not fully overlap with earlier findings on gray matter correlates of trait optimism [48,49,51] or related concepts [47]. In contrast to other investigations of optimism bias, here we used a competitive context, thereby possibly enabling slightly different mechanisms that rely on additional or distinct brain structures.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…As Blackburn and Epel (2017) put it, your cells are listening to your thoughts. Optimism and positive thinking are related to better mental and physical health (Lai, Wang, Zhao, Qiu, & Gong, 2020). Ongoing thoughts can influence the link between brain physiology and well-being.…”
Section: Optimismmentioning
confidence: 99%
“…Studying such predictive yield is worthwhile because it may enable the identification of the most important structural brain characteristics (e.g., of identified key regions in earlier research, such as ACC, insula, striatum, and PCC) to the strength of the manifested OB. Lai et al have addressed this issue to some extent in their study, where bilateral GMV of putamen correlated with trait optimism (i.e., the tendency to look positively into one's own future, which is not necessarily irrational as in OB) [14]. However, their primary findings were based on voxel-based morphometry with behavioral questionnaires of the life orientation test (LOT, as an indicator for trait optimism), and its results were only then confirmed by a predictive approach, as a post-hoc reliability strategy.…”
Section: Introductionmentioning
confidence: 99%